TOTAL HIP REPLACEMENT POSSIBILITIES FOR PATIENTS WITH SUFFERED BONE METABOLISM - T. B. Minasov; I. R. Gafarov; I. B. Minasov; K. Kh. Syrodgeov; K. K. Karimov (Креативная хирургия и онкология)
The results of clinic and X – ray monitoring after total hip replacement of patients with disturbed bone metabolism had been analyzed. Zoledronic acid effectiveness combined with calcium and Vit D was studied. Parameters of functional activity, life quality and DEXA monitoring had been researched. Thus we can conclude that short time treatment is effective for life quality and functional activity.